2005
DOI: 10.1007/s11055-005-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neurochemical lesioning of dopaminergic terminals in early ontogenesis on behavior in adult rats

Abstract: 6-Hydroxydopamine, which induces selective degeneration of the dopaminergic system of the brain, was given intraamniotically to rats on days 13 and 17 of intrauterine development at a dose of 75 microg/fetus. Similar experiments were performed with 6-hydroxydopamine on days 4 and 10 of neonatal life. Rats were subsequently reared and motor and emotional (dopamine-dependent) types of behavior were studied in adulthood, addressing behavior in the open field test, rotatory behavior, anxiety in an elevated cross m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In addition, as experimental exposure began early in this study (5 dpf), at a time at which neurogenesis was still underway and the nervous system was maturing (Kastenhuber et al 2010, McGraw et al 2012, Souza & Tropepe 2011, the phenotypes observed may reflect this early disruption. Similar effects have been demonstrated following the embryonic disruption of monoamine systems (Dennis et al 2013, Shabanov et al 2005, Silva et al 2013 or early exposure to silver or cadmium (Kusch et al 2008, Powers et al 2011. Such a delayed effect has also been demonstrated in zebrafish, following the exposure of embryos or larvae to PAH mixtures (Vignet et al 2014a), in rat, after perinatal exposure (Crépeaux et al 2012) and after the exposure of Pacific herring embryos to weathered crude oil (Carls et al 1999).…”
Section: Discussionmentioning
confidence: 60%
“…In addition, as experimental exposure began early in this study (5 dpf), at a time at which neurogenesis was still underway and the nervous system was maturing (Kastenhuber et al 2010, McGraw et al 2012, Souza & Tropepe 2011, the phenotypes observed may reflect this early disruption. Similar effects have been demonstrated following the embryonic disruption of monoamine systems (Dennis et al 2013, Shabanov et al 2005, Silva et al 2013 or early exposure to silver or cadmium (Kusch et al 2008, Powers et al 2011. Such a delayed effect has also been demonstrated in zebrafish, following the exposure of embryos or larvae to PAH mixtures (Vignet et al 2014a), in rat, after perinatal exposure (Crépeaux et al 2012) and after the exposure of Pacific herring embryos to weathered crude oil (Carls et al 1999).…”
Section: Discussionmentioning
confidence: 60%
“…This possibility is supported by a host of studies underscoring the key role of DA in behavioral disinhibition (Black et al , 2002; Megens et al , 1992; van Gaalen et al , 2006) and anxiolysis (Shabanov et al , 2005; Picazo et al , 2009). Previous studies have shown that PEA induces modification of the DA signaling, which may play a role in the behavioral responses mediated by this trace amine (Kuroki et al , 1990; Sotnikova et al , 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Shabanov et al . (2005) examined the effects of prenatal (days 13–17 of pregnancy) and early postnatal (days 4–10) systemic 6‐OHDA lesions in rats.…”
Section: Studies Examining the Effects Of Lesions (See Also Table 7)mentioning
confidence: 99%